Effects of boundary condition and cell structure on dynamic axial crushing honeycomb - Tsutomu UMEDA; Koji MIMURA (Mechanical Engineering Journal, 2018)
The dynamic axially crushing behavior of metal honeycombs was studied with placing emphasis on the effects of boundary condition and cell structure on its characteristics as an energy absorber. Numerical honeycomb models of some metal foil materials were made by taking the plastic deformation of adhesive layer, the failure of adhesively-bonded joint and the initial imperfection into account. Then, firstly, the foil material and the branch angle φ of cell geometry were varied to examine the effects on the crushing behavior and the energy absorption capacity. Secondly, to investigate the effects of boundary condition on the crushing mode and the energy absorption capacity, some boundary conditions such as the fixed end condition, the contact condition at the upper and lower ends and the periodic boundary condition at the side surfaces were applied to the honeycomb model. Typical calculated results under different strain rates and geometric conditions were compared with the corresponding experimental results, and the effects of material properties on the mean buckling stress were discussed. It was found that for the material with strain rate dependence, the stress increment of crushing honeycomb due to increasing the strain rate was 30-40 % as large as that of the material itself. Small φ causes different deformation mode of wrinkles, and the mean buckling stress σm decreased about 50 % by changing φ from 120° to 30°. Furthermore, small-scale honeycomb with small φ is easy to be affected by free edges considerably at φ = 60°. The oblique loading condition caused the transition from axial collapse to bending collapse so that at the crush angle of 45° σm became 30-50 % smaller than that under the vertical loading condition, while the effect of the direction of oblique load on σm is not so large.